Lack of knowledge in financial planning contribute to poverty / Adham Ramli - Ramli, Adham (2019)
Lack of knowledge and awareness among the people has caused the Islamic financial system such as the islamic banking institution and Takaful industry to be slower as compared to the conventional system. The Islamic scholar's contribute in the created and establishment of financial institution to compete with the conventional system. This is very important things as a Muslim which is in fulfilling a religious obligation and for the financial planning. The lack of knowledge and understanding cannot be solved simply by only urged the participants in contributing their wealth without giving them a better understanding of Financial Planning. It is very vital to ensure the society have a clear understanding about Financial Planning which can be influencing them to make the contribution as a participant for their financial planning. This research aim is to identify are the lack of knowledge is the factors that contribute to urban poverty, the level acceptance among the society, the perception of Muslim consumers towards Islamic financial system and also to analyse the attitude of Kuala Lumpur Citizen in expenses their money. This research is based on the data obtained from a survey questionnaire that polled Kuala Lumpur Citizen Perception towards financial planning. Data were processed and analysed using SPSS software version2.0.